Listening to grass-hoppers : field notes on democracy - Roy, Arundhati (New Delhi : Hamish Hamilton an imprint of Penguin Books, 2009)
With special reference to various topics related to anti-democratic issue of communalism, division between Muslims and Hindus, state sponsored terrorism, terrorist attacks, and emergence of Hindutva in India; articles previously published in several journals and books.
Includes bibliographical references (p. 211-238) and index.
Keywords: Communalism -- India; Hindus -- India; Muslims -- India; Hindutva -- India; Terrorism -- India